Ornithine enantiomers modulate essential oil yield and constituents and gene expression of monoterpenes synthase in Salvia officinalis under well-watered and drought stress conditions - Maryam Mohammadi-Cheraghabadi; Faezeh Ghanati; Naser Karimi; Mansour Ghorbanpour; Saeid Hazrati (BMC Plant Biology)
Abstract The impact of drought stress on plant growth, development, and productivity presents a significant challenge in various environments worldwide. The exogenous application of polyamines as osmotically active materials plays a crucial role in enhancing plant tolerance to environmental stress. In this study, we examined the effects of L- and D-enantiomers of ornithine (0 and 1 mM) under both well-watered and drought stress conditions on the growth traits, essential oil (EO) yield, and composition, gene expression, and total phenolic and flavonoid content of Salvia officinalis. The experiment was designed as a factorial experiment using a completely randomized design with three replications. The results demonstrated that drought stress led to a decrease in plant biomass and an increase in EO content, chemical profiles of the EO, and total phenolic and flavonoid content compared to the respective control values. However, the exogenous supplementation of ornithine particularly D-ornithine resulted in enhanced stem, leaf, and total plant biomass, a 20% increase in EO content, and a 75% increase in yield. Additionally, these were increases of 11.76% in total phenol and 70%, 105.66%, and 114.28% in flavonoid content when compared to well-watered plants without ornithine supplementation. These improvements were strongly linked to growth enhancement, as evidenced by principal component analysis (PCA). The EO extracted from S. officinalis consisted of 22 compounds, primarily monoterpenes, including α-thujone (18.47–41.65%), camphor (15.05–25.17%), 1,8-cineole (10.12–21.6%), and β-thujone (6.23–21.2%). The percentage of these volatile compounds was found to be highest in D-ornithine-treated stressed plants compared to control conditions. The interaction between water availability and the application of D-ornithine and L-ornithine significantly influenced the expression of borneol diphosphate synthase (BS), sabinene synthase (SS), and cineole synthase (CS) under drought stress, with notable upregulation observed compared to normal growth conditions. Specifically, D-ornithine enhanced the expression of BS and SS by 45.29% and 113.63%, respectively, under drought stress, while both D-ornithine and DL-ornithine significantly increased CS expression. The present results suggest that D-ornithine may serve as a stress-protecting compound, increasing total phenol and flavonoids content, thereby enhancing the capacity of the antioxidant system and increasing EO compounds under drought stress.